ALIH KODE DALAM INTERKASI DI LINGKUNGAN PONDOK PESANTREN ULIL ALBAAB: KAJIAN SOSIOLINGUISTIK - Baiq Yulia Kurnia Wahidah; Djatmika Djatmika; Sri Marmanto (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2019)
This research describes the use of code switching into four domains and the code switching form in the Ulil Albab boarding schools Sasak. This study applied qualitative approach and used sociolinguistics as the basis of interpretation. Subject of this study were santri and teachers in the pesantren.  The primary data were observed from the classroom settings and daily activities in the pesantren, when santri and teachers spoke in four languages: Indonesian, English, Arabic, and Sasak language.  Data were analyzed using  theory of code switching and code mixing from Dell Hymes.  The study revealed  that code switching occurred 138 tokens and  conversation appeared at 75%. Code switching was used as to give better comprehension to partnered-speaker.